2017
DOI: 10.1016/j.cct.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting for covariates in evaluating markers for selecting treatment, with application to guiding chemotherapy for treating estrogen-receptor-positive, node-positive breast cancer

Abstract: In many clinical contexts, biomarkers that predict treatment efficacy are highly sought after. Such treatment selection or predictive biomarkers have the potential to identify subgroups most likely to benefit from the treatment, and may therefore be used to improve clinical outcomes and reduce medical costs. A methodological challenge in evaluating these biomarkers is determining how to take into account other variables that predict clinical outcomes, or that influence the biomarker distribution, generically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We found that the RS category was independently associated with chemotherapy recommendation in pN1 patients in our study, which was in consistency with previous findings 2224 . For low RS pN1 patients, 40.68% (24/59) were exempt from chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the RS category was independently associated with chemotherapy recommendation in pN1 patients in our study, which was in consistency with previous findings 2224 . For low RS pN1 patients, 40.68% (24/59) were exempt from chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…It is common in clinical trials that only a subgroup of treated patients may benefit from an experimental therapy [ 54 57 ]. Identifying these subgroups would allow tailoring of treatment, avoiding costly or toxic treatment of individuals who will not benefit.…”
Section: Overview Of Innovative Methods For Immune-mediated Inflammatory Disease Trialsmentioning
confidence: 99%
“…It is common in clinical trials that only a subgroup of treated patients may bene t from an experimental therapy (52)(53)(54)(55). Identifying these subgroups would allow tailoring of treatment, avoiding costly or toxic treatment of individuals who will not bene t. To identify such subgroups, predictive biomarkers are required.…”
Section: Use Of High-dimensional Data To Stratify Patients: Adaptive mentioning
confidence: 99%
“…What was the length of patient recruitment (in weeks)? 2 Median: 96 IQR: [55,120] Range: [16,296] What was the primary endpoint timepoint (in weeks)? 1 One article used a sequential multiple assignment randomised trial design with an interim futility assessment.…”
Section: Biomarker Adaptivementioning
confidence: 99%